2006
DOI: 10.1051/0004-6361:20041980
|View full text |Cite
|
Sign up to set email alerts
|

Stable magnetic fields in stellar interiors

Abstract: We investigate the 50-year old hypothesis that the magnetic fields of the Ap stars are stable equilibria that have survived in these stars since their formation. With numerical simulations we find that stable magnetic field configurations indeed appear to exist under the conditions in the radiative interior of a star. Confirming a hypothesis by Prendergast (1956, ApJ, 123, 498), the configurations have roughly equal poloidal and toroidal field strengths. We find that tori of such twisted fields can form as rem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

30
461
5
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 367 publications
(499 citation statements)
references
References 29 publications
30
461
5
3
Order By: Relevance
“…This analytical solution is thus similar to the axisymmetric non force-free relaxed solution family obtained by Braithwaite & Spruit (2004) and Braithwaite & Nordlund (2006). Its stability has now been demonstrated by Duez et al (2010a, see also Duez et al in this volume).…”
Section: Relaxed Non Force-free Configurationssupporting
confidence: 81%
See 2 more Smart Citations
“…This analytical solution is thus similar to the axisymmetric non force-free relaxed solution family obtained by Braithwaite & Spruit (2004) and Braithwaite & Nordlund (2006). Its stability has now been demonstrated by Duez et al (2010a, see also Duez et al in this volume).…”
Section: Relaxed Non Force-free Configurationssupporting
confidence: 81%
“…It was suggested by Prendergast (1956) that a stellar magnetic field in stable axisymmetric equilibrium must contain both poloidal (meridional) and toroidal (azimuthal) components, since both are unstable on their own (Tayler 1973;Wright 1973). This was confirmed recently by numerical simulations by Braithwaite & Spruit (2004); Braithwaite & Nordlund (2006);Braithwaite (2008) who showed that initial stochastic helical fields evolve on an Alfvén timescale Dynamics of fossil magnetic fields in massive star interiors 161 into stable configurations: axisymmetric and non-axisymmetric mixed poloidal-toroidal fields were found. This phenomenon well known in plasma physics is a MHD turbulent relaxation (i.e.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Braithwaite & Spruit (2004) and Braithwaite & Nordlund (2006) have shown that the combination of the Cowling instability with rotation and meridional circulation may lead to major reorganisation of the internal flux. Similarly, theoretical computations suggest how atmospheric chemical peculiarities might develop and evolve with time through the main sequence phase, but so far these computations have not succeeded in reproducing observed abundance patterns in detail (Babel & Michaud 1991).…”
Section: Introductionmentioning
confidence: 99%
“…One possibility is that, at the end of the MS and its associated dynamo, the magnetic field is able to evolve into a stable configuration only in ≈50% of the cases. The evolution of magnetic fields into stable magnetic configurations has been studied (Braithwaite & Nordlund 2006), but it is difficult to make detailed predictions as the outcome depends on the complex initial conditions of the magnetic configuration left by turbulent convection, in particular magnetic energy and helicity (Braithwaite 2008). Moreover, these theoretical calculations do not include a compositional stratification, which instead might play an important role in confining the magnetic field after dynamo action ceases in the convective cores of stars.…”
mentioning
confidence: 99%